Rehabilitation within pre-crime interventions: The hybrid criminology of social crime prevention and countering violent extremism - Heath-Kelly, Charlotte (Theoretical criminology, 2023)
Criminological literature frequently argues that the rehabilitative penological paradigm of the 20th century (‘penal welfarism’) has been replaced by pre-crime, risk-based, ‘new penology’. Under the conditions of social and economic neoliberalism, it is claimed, the commitment to rehabilitating individuals has been withdrawn. In this article, we explore the curious persistence of rehabilitation—enacted within crime prevention and countering-violent-extremism programmes. We show that rather than ‘new penology’ replacing ‘penal welfarism’, the history of social crime prevention programmes demonstrates the presence of a ‘hybrid penology’. Here, rehabilitation was brought into the pre-criminal space and practised upon pre-delinquents. This pre-emptive rehabilitation of at-risk subjects pervaded preventive policy in both Western Europe and the socialist Former Yugoslavia. In both case studies, this logic of pre-crime rehabilitation then transferred into the counterterrorism sector—with ideological dissidence identified as the threshold for reform-oriented intervention. Rehabilitation remains with us, warped by the turn to pre-emption.